Building Environmentally Sustainable Corporate Identity on the Internet : A Multimodal Case Study of the Corporate Social Responsibility Discourse on the Corporate Websites of Finnair and VR - Miettinen, Pinja (My University, 2026)
The aim of this thesis is to analyse and compare how two Finnish transport industry companies, Finnair and VR, multimodally create environmentally sustainable corporate identity on their corporate website sections focusing on Corporate Social Responsibility through text and image. The analysis of the text is completed by examining locutionary and illocutionary acts present in the text of the websites following the methodologies of Speech Act Theory presented by Austin (1962) and the further division of the illocutionary acts presented by Searle (1976). The study of the images, then, is done through a proposed new methodology that is inspired by Kjørup’s (1974, 1978) theory of image acts and utilises Unsworth and Cléirigh’s (2008) methodology of analysing image-text relationships to reveal the illocutionary points of images according to Searle’s classification. The results of this thesis indicate that both companies discuss environmental sustainability in great detail on their websites to build environmentally sustainable corporate identity, but the contents of the locutionary acts differ as Finnair focuses more on future environmental actions whereas VR focuses more on the current greenness of the company. What comes to illocutionary acts, in both cases assertive acts were the most common, but Finnair also used more commissive acts in comparison to VR. The visual analysis, then, revealed that both companies use images to illustrate their environmental doings explained in the text. As the images relate to the assertive speech acts, I argue that the images also have assertive illocutionary points.
Keywords: Speech Act Theory, Corporate Social Responsibility, corporate identity, corporate communications, corporate website